Infant health and longevity: Evidence from a historical trial in Sweden - Sonia R. Bhalotra; Martin Karlsson; Therese Nilsson (University of Essex, Institute for Social and Economic Research (ISER), 2015)
This paper investigates the potential of an infant intervention to improve life expectancy, contributing to emerging interest in the early life origins of chronic disease. We analyse a pioneering program trialled in Sweden in the 1930s, which provided information, support and monitoring of infant care. Using birth certificate data from parish records matched to death registers, we estimate that the average duration of program exposure in infancy led to a 1.54% point decline in the risk of infant death (23% of baseline risk) and a 2.37% decline in the risk of dying by age 75 (6.5% of baseline risk).
Keywords: I15; I18; H41; 330; infant health; life expectancy; early life interventions; program evaluation